2004
DOI: 10.1007/s11165-004-3229-4
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of Analogical Explanations: High School Physics Teachers Use in Kenya

Abstract: This paper is about a study into the nature of analogies recorded from three Form 2 (Grade 10) classes in Kenya, instructed by three physics teachers. Through a case study method involving classroom observation, several analogies were recorded and analysed. These analogies were predominantly environmental (drawn from students' socio-cultural environment) and anthropomorphic (life and human characteristics ascribed to analogues involving familiar concepts). A small number were scientific (those in which analogu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
15

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 32 publications
0
32
0
15
Order By: Relevance
“…As pointed out by Mpofu (2002), Zimbabweans' lives are influenced by both indigenous cultural values and the envied and sometimes maligned Anglo-Western values. Nashon (2004) alludes to the cognitive conflict, which African students may experience in learning science because of using two different paradigms: indigenous (cultural) and Western scientific thought.…”
Section: Context Of Ndebele Cultural Views Of Giftednessmentioning
confidence: 99%
“…As pointed out by Mpofu (2002), Zimbabweans' lives are influenced by both indigenous cultural values and the envied and sometimes maligned Anglo-Western values. Nashon (2004) alludes to the cognitive conflict, which African students may experience in learning science because of using two different paradigms: indigenous (cultural) and Western scientific thought.…”
Section: Context Of Ndebele Cultural Views Of Giftednessmentioning
confidence: 99%
“…Zacharia used the PredictObserve-Explain sequence with the teachers in relation to both the computer-based simulations and more traditional textbook-based assignments on the content, and found that when the teachers interacted with the computer-based simulations the explanations they constructed were richer, more detailed, scientifically more accurate and involved more formal reasoning. Nashon (2004) recorded the kinds of analogies used by three Kenyan Grade 10 physics teachers. He determined that many of the analogies used were connected to the students' lifeworlds while a number were also anthropomorphic in nature.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There has been some research attention paid to the use of analogies in physics teaching explanations (e.g. Nashon, 2004;Podolefsky & Finkelstein, 2007;Thagard, 1992;Treagust & Harrison, 1999, 2000. All the teachers in the study used analogies extensively.…”
Section: Table One -Distinctive Explanatory Features Related To Specimentioning
confidence: 99%
“…Research spanning almost half a century (Aikenhead 1996;Aikenhead and Jegede 1999;Ausubel 1968;Clement 1993;Cobern 1996;Cobern et al 1995;Driver 1989;Driver and Easley 1978;Kelly 1955;Nashon 2003Nashon , 2004Piaget and Inhelder 1969;Pittman 1999) shows that students bring prior knowledge about the concepts, phenomena or experiences encountered during classroom instruction and use this prior knowledge to interpret new encounters or phenomena. Various instructional models have been proposed for enabling students to process this new information in light of the prior conceptions they hold.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The messages used in media campaigns, then, transmit information about HIV/AIDS and other sexuality issues through the use of metaphors, analogies and similes. But research has shown that such expressions are subject to multiple interpretations that are in large part influenced by prior understandings (Nashon 2003(Nashon , 2004Zeitoun 1984).…”
Section: Introductionmentioning
confidence: 99%